ISSUES OF USING FOREIGN EXPERIENCE IN THE INTRODUCTION OF INNOVATIONS BASED ON DIGITAL TECHNOLOGIES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article considers the digital economy as the main factor in the development of the country's economic sectors. The programs of the digital economy of various foreign countries have been analyzed. Methods of effective organization and establishment of the digital economy have been studied. One of the most important conditions for the effective development of the leading branches of human activity in the digital economy – based on the fact that the main emphasis is placed on the formation of the appropriate institutional environment-for the successful development of the digital economy, the basic conditions for the use of reforms, personnel and knowledge have been established.